Liquid metal polymer composite: Flexible, conductive, biocompatible, and antimicrobial scaffold. Issue 5 (15th December 2021) - Houshyar, Shadi; Rifai, Aaqil; Zizhou, Rumbidzai; Dekiwadia, Chaitali; Booth, Marsilea A.; John, Sabu; Fox, Kate; Truong, Vi Khanh
Abstract: Gallium and its alloys, such as eutectic gallium indium alloy (EGaIn), a form of liquid metal, have recently attracted the attention of researchers due to their low toxicity and electrical and thermal conductivity for biomedical application. However, further research is required to harness EGaIn‐composites advantages and address their application as a biomedical scaffold. In this research, EGaIn‐polylactic acid/polycaprolactone composites with and without a second conductive filler, MXene, were prepared and characterized. The addition of MXene, into the EGaIn‐composite, can improve the composite's electrochemical properties by connecting the liquid metal droplets resulting in electrically conductive continuous pathways within the polymeric matrix. The results showed that the composite with 50% EGaIn and 4% MXene, displayed optimal electrochemical properties and enhanced mechanical and radiopacity properties. Furthermore, the composite showed good biocompatibility, examined through interactions with fibroblast cells, and antibacterial properties against methicillin‐resistant Staphylococcus aureus . Therefore, the liquid metal (EGaIn) polymer composite with MXene provides a first proof‐of‐concept engineering scaffold strategy with low toxicity, functional electrochemical properties, and promising antimicrobial properties.